Applying Semantic Web technology to the integration of corporate information. (27th December 2005) - Barrett, Tom; Jones, David; Yuan, Jun; Uschold, Mike
The emergence of web standards for representing the semantics of information has enabled a new level of integration of information resources. In this paper we will discuss a number of issues related to semantic integration and the techniques we employed for integrating disparate resources. We will detail our approach, which includes the use of ontologies, information mapping and distributed queries. We will also show how we used RDF to represent different types of metadata within the system. Additionally, we will discuss some techniques for using certain types of semantic information to assist in the navigation of very large search spaces. In particular we will show how the tools we developed support an interactive querying paradigm for browsing information.